A developmental perspective on decision making in sports - Marasso, D.; Laborde, S.; Bardaglio, G.; Raab, M. (International Review of Sport and Exercise Psychology, 2014)
The aim of this narrative review article is to provide a developmental perspective on decision making in sports. Although there is extensive research investigating the influence of decision making on sports performance, research examining how athletes' decision making develops is almost non-existent. We take a developmental perspective to advance our understanding of the theoretical foundations, empirical findings, and practical applications of research on decision making in sports. We provide a framework for understanding choices in sports over the course of ontogenetic development. This framework can be used to guide future research and applications.